NEPHRECTOMY BY PAPILAR CARCINOMA OF TRANSITIONAL CELLS (UROTELIAL) HIGH GRADE NOT INVASIVE CASE STUDY - Nader, Jorge Daher; López, Lcda. Alida Vallejo; Gómez, Xavier Chan (International Journal of Research -GRANTHAALAYAH, 2019)
Cancer is one of the main causes of morbidity and mortality worldwide, it is produced by the transformation of normal cells into tumor cells in a multiple stages process that can progress to a precancerous lesion to a malignant tumor that can spread through the blood and lymphatic system causing metastasis. The incidence of kidney cancer seems to be increasing, in adults, it begins in the kidneys and can spread to the entire urinary tract that surrounds distant organs or places, renal cell carcinoma is the most common type of kidney cancer and represents approximately 90 percent of cancers tumors. The present study evidences the case of a patient who comes to medical services when the problem shows symptoms. Objective - To describe the renal cancer case of a patient with papillary transitional cell carcinoma who was operated to remove a kidney tumor in order to prevent it from triggering in severe states. Method - The literature on cancer and cancer patients has been reviewed, in the urinary system the data of a case that generated kidney tumor surgery performed in a 63-year-old female patient has been reviewed. Result - High-grade, non-invasive papillary transitional cell carcinoma (UROTELIAL) can occur, in patients altering the quality of life of people, if it is detected and treated in time complications can be avoided Conclusion - It is essential to identify the risk factors and possible causes that can trigger this type of pathology, the information collected is expected to be useful to professionals and to contribute as an alert to detect health problems in patients early.